Gambaran Tingkat Pengetahuan Ibu Tentang Gizi Anak Toddlers (1-3 Tahun) Di Desa Mumbulsari Kecamatan Mumbulsari Kabupaten Jember Tahun 2012 - Trisna Pangestuning Tyas (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2013)
Toddlers age is one of the stages in the grows five. In many community issues that emerged is the lack of knowledge about the mother's nutrition and how the provision of nutritious food for their children. This research aims to find out the level of maternal nutrition on children aged toddlers in the Village District Mumbulsari Jember Regency Mumbulsari. Design is the method used descriptive. Number of respondents population 253 people with some sample mothers who have children the age of toddlers in the Village District Mumbulsari Jember Regency Mumbulsari namely some 155 people. Collecting data is done using a questionnaire. Tabulated and then the data presented in the form of a frequency distribution table. Results of research shows that almost half the number of 68 respondents (43.87%) included in the criteria is quite knowledgeable.This is influenced by the work of the respondents some of all respondents as the mother of the household respondents and the level of education that is almost entirely a primary school.